Using peer feedback to improve students’ writing - Dương, Thị Phương Thảo (University of Languages and International Studies, 2017)
The main aim of this action research carried out at Haiphong Community College (HPCC) is to investigate whether teaching sentence writing through students’ peer feedback is effective or not, the way in which students’ response to their peers’ writings.